Deriving pediatric nerve conduction normal values in the very young (<3 years). Issue 1 (January 2020) - Jabre, Joe F.; Pitt, Matthew C.; Smith, Ralph
Highlights: Pediatric EMG is an essential part of the workup of children with neuromuscular disorders. The paucity of normal values in the <3 years old poses a limitation in the analysis of their tests. The e-norms method is a fast and efficient method to derive a lab's own normal values. Abstract: Objective: This work describes our efforts to obtain nerve conduction studies normal values in a pediatric cohort between birth and 3 years of age using the extrapolated norms or e-norms method. Interpretation of these studies poses major challenges when no reliable normal values can be found in the literature. Methods: The e-norms method was used to derive a reference range of upper and lower extremity sensory and motor nerve conductions normal values from a pediatric cohort referred to an EMG Laboratory for nerve conduction studies. Results: E-norms were calculated for Median, Ulnar, Superficial Peroneal, Sural, and Medial Plantar sensory studies, and for Median, Ulnar, Peroneal, and Tibial motor studies. Conclusions: Pediatric electrodiagnostic testing is a very challenging undertaking. The ability to obtain and use normal values from the neurophysiologist's own referral pool adds great value to their diagnostic work-up. Significance: EMG and nerve conduction studies can yield invaluable information in the diagnostic work-up of young infants. Using the e-norms method improves on the analysis and interpretation of electrophysiological studies in this age group.